Pengembangan Media Labirin Berbasis Digital Untuk Menstimulasi Kemampuan Visual Spasial Anak Usia 5-6 Tahun - Faiza Nadhifa; Winda Sherly Utami; Annisha Erdaliameta (Jurnal Bina Ilmu Cendekia, 2026)
This study was motivated by the low visual-spatial abilities of children, such as difficulties in recognizing directions, completing tasks independently, and understanding objects from different points of view. The purpose of this study was to determine the effect of digital maze media on the visual-spatial abilities of children aged 5–6 years at TK Mutiara Ibu Kota Jambi and to provide an innovative digital learning medium that supports the development of visual-spatial skills in early childhood. This study also contributes to the growing body of research on technology-based learning in early childhood education by providing empirical evidence regarding the effectiveness of digital maze media in enhancing children's visual-spatial abilities. This study used an experimental method with a One Group Pretest-Posttest Design. The sample consisted of 11 children in group B3 selected through purposive sampling. Data were collected using an observation sheet, while data analysis used normality tests, homogeneity tests, and paired sample t-tests. The results showed that tcount > ttable (37.183 > 2.228), indicating that H₀ was rejected and Hₐ was accepted. The effect size value was 9.64, which was categorized as a strong effect. Therefore, it can be concluded that digital maze media had a positive and significant effect on the visual-spatial abilities of children aged 5–6 years at TK Mutiara Ibu Kota Jambi.